The correlation of handover and the performance of nurse - Susanti; Etlidawati (Proceedings Series on Health & Medical Sciences, 2020)
The means of communication between nurses and other medical teams through handover must be recorded properly. Communication dysfunction during the handover may have an effect on nursing documentation such as errors in action planning.This study aimed to determine the correlation between the implementation of handover and the performance of nurses in the inpatient room of Banyumas Hospital.This research was a descriptive analytical with a cross sectional approach research. The sample of nurses on duty in the inpatient room were 67 persons. Data were collected by using a questionnaire and the analysis of research data were completed by the Chi Square test.Most of the nurses are female totaled 43 persons (64.2%), 65 persons are married (97.0%) and 41 persons are civil servants (61.2%). Most of the respondents have a DIII Nursing education (41.2%). The average age of the nurse is 33.67 years with an average working period of 8.51 years. Most of handover are in the good category, 42 persons (62.7%). Most of the nurses' performance are in good category totaled 49 persons (73.1%). There is a correlation between the implementation of handover with the performance of nurses in the inpatient room of Banyumas Hospital (p = 0.000).In conclusion better implementation of handover will improve the performance of nurses in the inpatient room of Banyumas Hospital.